(3GdLHQ hGdebGHdIs - (3eMeO Hf ehSi GdNhGQRej, CHh YHO Gddg,J (B232 (3g` s ((3eMeO Hf SYjO s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg HeG gh Cgdg hde jRd GdYdeGA ai GdCRefI GdNGdjI jcJHhf GdcJH eeG jUahfg ef Uaha GdYde s
(3BNQgG (B:s
(3ajHbi GdhUjI hgj eGFJGf hKdGKg hjbi ddhQKI Gda hJSYeGFI hJSYI hYTQhf hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3JfbU gPg GdfSNI Yf GdfSNI GdSGHbI (B4 (3CHhGHs
(3fSNI KGfjIZes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs